Custom ('Urf) as a marginal discourse in the formulation of Islamic law : myth or reality? : with special reference to Ibn 'Abidin's discourse on 'Urf - Sitoto, Tahir Fuzile T (Department of Religious Studies, 2014)
Bibliography: leaves 84-87.